An Overview of The Spinal Metastasis Pain with Opioid Therapy and The Affecting Factor - Djohansjah, Joice Rosewitasari Aryanti; Andriani, Rini; Aninditha, Tiara; Sofyan, Henry Riyanto (Indonesian Journal of Cancer, 2024)
Background: Spinal metastasis is the most frequent type of spinal tumor. Opioid is the first line of treatment for cancer pain despite a multitude of side effects. This study aimed to evaluate the effectiveness of opioids as the latest ladder in the treatment of spinal cancer pain. Methods: A retrospective cross-sectional study was performed comprising 89 spinal metastasis patients at the National Cancer Centre, Dharmais Hospital from November 2021 to March 2022. The demographic and clinical data were retrieved from medical records. This study used the Numerical Rating Scale (NRS) to evaluate the improvement of pain. The change of NRS ≥ 2 was considered significant. The data was analyzed using bivariate (Wilcoxon, Mann-Whitney, and Fisher Exact test) and multivariate (linear regression) analysis. Results: A total of 89 subjects were included in the study (median age = 51 years, 57,3% females). There was a significant decrease in the severity of cancer pain (p0.005) between admission (initial NRS 7) and treatment completion (final NRS 2) in the first hospitalization of all groups. There was no correlation between the clinical characteristics of the participants and the NRS score determined upon admission and at the end of the course of treatment. Conclusions: There was a significant improvement in the cancer pain intensity in the subjects with spinal metastasis cancer pain who received opioid naive therapy.